2020
DOI: 10.1002/ange.202009719
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Solid Solution Formation Triggers the Propagation of Homochirality

Abstract: Propagation of homochirality plays a crucial role in the discussion on the origin of life. We investigated the role of structurally related enantiopure additives in chiral symmetry breaking during reactive crystallizations. We demonstrate that symmetry breaking can be driven towards the same absolute configuration as the additive if this additive forms an enantiospecific solid solution with the racemate. We observe two antagonistic processes: enantiospecific growth inhibition directs symmetry breaking to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…59,60 Compound 2 crystallizes as a conglomerate and also readily undergoes racemization in the presence of DBU in methanol. 39,48,61 To demonstrate that the chiral amplification is also independent of the racemization catalyst, we use the organic base 1,1,3,3-tetramethylguanidine (TMG), which we show racemizes 2 as well (Figure S1). As proof of generality, akin to the abrupt cooling experiments for 1, we create a supersaturated solution of (RS)-2 (30 mg/mL) in the presence of 100 μL/mL TMG at 20 °C.…”
Section: Journal Of Thementioning
confidence: 99%
“…59,60 Compound 2 crystallizes as a conglomerate and also readily undergoes racemization in the presence of DBU in methanol. 39,48,61 To demonstrate that the chiral amplification is also independent of the racemization catalyst, we use the organic base 1,1,3,3-tetramethylguanidine (TMG), which we show racemizes 2 as well (Figure S1). As proof of generality, akin to the abrupt cooling experiments for 1, we create a supersaturated solution of (RS)-2 (30 mg/mL) in the presence of 100 μL/mL TMG at 20 °C.…”
Section: Journal Of Thementioning
confidence: 99%
“…29−36 However, there are no reports of conglomerates that can handle many additives in any scenario to control the chirality of crystal growth. 37 For example, in the preferential crystallization of asparagine and glutamine without dynamic racemization, there is a pioneering report in which the reversal effect controls mirror images in which several amino acids are preferentially obtained. 38 In dynamic crystallization, it has been reported that, of the many additives tested during optical resolution by crystallization of binaphthyl, only mandelic acid and tartaric acid could perform chirality control.…”
mentioning
confidence: 99%